2012
DOI: 10.1002/j.2168-0159.2012.tb05717.x
|View full text |Cite
|
Sign up to set email alerts
|

9.1: WITHDRAWN: 9.2: New Threshold Voltage Compensation Pixel Circuits in 13.5‐inch Quad Full High Definition OLED Display of Crystalline In‐Ga‐Zn‐Oxide FETs

Abstract: We devised a 5Tr+1C threshold voltage compensation pixel circuit that operates even with a normally-on transistor. Variations in threshold voltage can be reduced to 25 to 30%. We fabricated a 13.5-inch quad full high definition (QFHD) OLED display, which has a top-emission structure using white tandem OLEDs with color filters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 12 publications
1
27
0
1
Order By: Relevance
“…In the conventional VP circuits with the so-called "diode-connected" V TH sensing scheme, the compensation is limited when the V TH is a negative value [25], [26]. However, the compensation can still work well in the proposed CBVP circuit as it is current sensed.…”
Section: A Compensation Results and Analysismentioning
confidence: 91%
“…In the conventional VP circuits with the so-called "diode-connected" V TH sensing scheme, the compensation is limited when the V TH is a negative value [25], [26]. However, the compensation can still work well in the proposed CBVP circuit as it is current sensed.…”
Section: A Compensation Results and Analysismentioning
confidence: 91%
“…1), the I off is further improved by an order of magnitude from $1 Â 10 À13 A/lm to 2.5 Â 10 À14 A/lm. It is suggested that off-state current may be related to c-axis aligned crystallization, which have been reported [13]. From C-V (dielectric constant of Al 2 O 3 $7.6) and I-V curves of Al 2 O 3 MIM capacitor (see inset of Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Recently, a c-axisaligned IGZO channel has been implemented in thin film transistor (TFT) process. The c-axis-aligned IGZO TFT featured a low off-state current and large on-off ratio [13] that showed the potential for developing new applications including active matrix liquid crystal display (AMLCD) or active matrix organic light emitted diode (AMOLED).…”
Section: Introductionmentioning
confidence: 99%
“…11,12) The CAAC-IGZO transistors with such properties have been applied to a liquid crystal display with high definition and an organic electroluminescence (EL) display. [13][14][15][16][17] In addition to the display application, the CAAC-IGZO has found application to low power consumption LSIs such as a nonvolatile memory, [18][19][20][21][22] a normally-off central processing unit (CPU), 23,24) a field-programmable gate array (FPGA), 25) and an image sensor, 26,27) has been proposed.…”
Section: Introductionmentioning
confidence: 99%